The First Decade of Effort: Progress Toward a Hospital Information System at the UCLA Hospital, Los Angeles, California - Lamson, B. G.; Russell, W. S.; Fullmore, J.; Nix, W. E. (Methods of Information in Medicine, 1970)
Total information and communication systems within hospitals have been designed, but successful complete implementation, to date, has not been achieved. Limited applications with both patient medical data, notably in the clinical laboratories, and in the hospital accounting offices have been numerous. Although total programs are not yet a reality, it is apparent that the computer will serve ultimately many communication requirements, both medical and financial, within the hospital.Sound hospital management requires that costs of all component operations be known in order that value judgments concerning worth and efficiency may be made. Accrual accounting systems which match revenue and expense over the same time period are a prerequisite. Cash and modified cash hospital accounting cannot provide current reliable data for sound decision making.Costs of hospital operations cannot be evaluated unless related to the characteristics of the patient service load. Average per diem costs mean little except when large similar populations of patients are being compared. A modern hospital accrual accounting system should be able to provide information concerning the costs of caring for specific diseases in patients with known age and sex and disease severity characteristics. Without information of this type, it will not be possible to objectively evaluate alternative systems of financing and organizing patient care.Medical record management offers the promise of prospective use of patient disease information in the planning and scheduling of facilities. The prose content of medical record summaries, such as diagnostic statements in tissue pathology, radiology, and admission and discharge diagnoses, may be susceptible to non-coded, full prose input into computer controlled diagnostic files. Thesauri in the several medical specialties will be necessary for this achievement.There is little immediate prospect for complete hospital communication systems that can be made available as a package to any hospital without substantial local alteration. Pilot projects in teaching centers should be viewed for the time being as opportunities to define objectives, evaluate feasibility, and determine degree of risk and expense.A brief survey of applications in the United States which have been successfully implemented or which appear suitable for successful implementation is recorded.Eleven general principles which have been associated with successful implementation of computer applications within the UCLA Hospital are enumerated.